Refugees in Poland: Selected Issues in Research - Gałka, Jadwiga (Bulletin of Geography. Socio-economic Series, 2009)
Since the beginning of the 1990s, there has been a steadily growing influx of foreign refugees in Poland. Poland's ratification of the Geneva Convention in 1991 and the New York Protocol in 1991 made it necessary to create a properly functioning refugee protection system in the country. The purpose of this work is to describe the dynamics of refugee influx in Poland from 1992 to 2007 as well as to analyze whether existing forms of legal stay are functioning properly in Poland. Furthermore, the work attempts to delve into key issues associated with the social integration of refugees in Poland.